A population study of nypa fruticans (arecaceae) on Carey Island, Malaysia / Nasrin Asle Zaeim - Zaeim, Nasrin Asle (2011)
Nypa fruticans (Arecaceae) is distributed in mangrove forests of South Asia especially in islands and the coastal area around Malaysia. It is one of the most versatile palms in terms of usage. A population study of N. fruticans at two sites using 3 plots was conducted in Carey Island, Malaysia. Aspects of demographic study of N. fruticans such as population structure, life stages of individuals, spatial distribution, reproductive phenology, growth rate, survivorship and environmental parameters such as water and soil quality were investigated in this study. Using the growth information, estimation of age would be possible. Four life developmental stages: Seedlings, juvenile, adult and mature are considered to assess growth of the individuals. Size structures of the species show high number of adults and mature trees compared to seedlings. No mortality is observed for trees during the study period. Regular and random distributions were observed for seedlings, juveniles and mature trees. Adults showed both regular and clumped dispersions because of the vegetative reproduction and suckering behavior. Seedlings are detected only in one location with significant difference in leaf production between plots. Rate of leaf production in juveniles is measured at 1 leaf per year. A significant difference in annual average of leaf production for adults (0.8-1.1 leaves per year) and mature trees (0.9-1 leaves per year) between two locations is observed. The total mean age of mature trees is approximately 31.4 - 34.8 years. Mean growth rates of spear leaf height increased from juvenile (55.5 cm per month) to mature trees with maximum spear elongation of 91cm per month; indicating that this species increases in height especially at adult and mature stage. The whole flowering cycle lasted between 8.2 to 9.6 months and 61 (53%) of 115 reproductive trees produced new inflorescence at a rate of one inflorescence per year which gives 60-120 fruits per plant. The soil texture at iii the study sites was silty – clay and average temperature of water in Carey Island is 27.3 ± 0.8 and pH is 6.4 ± 0.3. Significant correlations were observed between salinity and leaf production in juveniles and mature trees. Similarly, correlations were found between leaf production and heavy metals and nutrients at stages seedling and juvenile.